What is a Wookiee? - Buller, Laura; Simkins, Kate (DK, 2005)
Describes the main alien life forms which inhabit the Star Wars galaxy
"Lucas books."
Includes index
Keywords: Star Wars films / Juvenile literature; Star Wars / juvenile fiction; Star Wars / Juvenile fiction; Extraterrestrial beings / Fiction; Star Wars films; Star Wars fiction; Science fiction; Movie novels; Juvenile works; Kinderbuch